Training needs assessment of female teachers for utilization of information and communication technologies: https://doi.org/10.5281/zenodo.17048494 - Ayesha Karamat; Humara sharef; Zohaib Hassan Sain (`, 2025)
The study entitled “Training Needs Assessment of Female Teachers for Utilization of Information and Communication Technologies” was conducted in District Toba Tek Singh, Punjab, with the objective of identifying training requirements, benefits, challenges, and recommendations for improving induction training programs for female educators. The research population comprised 462 educators, including Elementary School Educators (ESE), Senior Elementary School Educators (SESE), and Secondary School Educators (SSE), from which a stratified random sample of 113 respondents was drawn using a 95% confidence level and 8% margin of error. Data were collected through a structured, pre-tested questionnaire, ensuring reliability and validity. Analysis was carried out using SPSS and MS Excel, and findings were presented in both tabular and graphical form. Results revealed that the most valued benefits of training were the development of communication skills (Mean = 3.96), improved performance (Mean = 3.81), and enhanced lesson planning methods (Mean = 3.73). Conversely, IT skills were rated lowest (Mean = 3.04), indicating limited integration of technology. Factors affecting training efficiency included management behavior (Mean = 4.19), trainee interest (Mean = 3.99), and participant involvement (Mean = 3.70), suggesting that human-related aspects were more influential than environmental or trainer-related factors. The impact of training on teaching efficiency was particularly strong in boosting confidence (Mean = 4.09), motivation (Mean = 3.98), and teaching skills (Mean = 3.88), while administrative aspects such as record management and financial utilization scored lower. Recommendations for improvement emphasized incentives for participants (Mean = 4.40), political neutrality (Mean = 4.20), and proper budget allocation (Mean = 4.15), alongside disciplined execution and use of modern technology. The study concludes that induction training programs play a vital role in enhancing teaching effectiveness, professional growth, and motivation of female educators, but require greater focus on digital competencies, resource provision, and neutral, well-structured delivery for long-term sustainability. Key Words: Need Assessment, ICTs, Training, Effect